Preproductive pathophysiological changes in non-pregnant Boer does inoculated with Corynebacterium pseudotuberculosis via intradermal, intranasal and oral routes - Othman, Aishatu Mohammed (2014)
An experimental study was conducted in non-pregnant Boer does inoculated with C.pseudotuberculosis via various routes with the objectives of determining the changes in hematology, biochemical, serum electrolyte, progesterone, estrogen, interleukin-1β, and interleukin 6 as well as pathological changes in the reproductive organs and their associated lymph nodes. A total of twenty (20) healthy non-pregnant Boer does were divided into 4 groups (1, 2, 3 and 4) of 5 does per group. Group 1 was kept unexposed. Group2, 3 and 4 were inoculated with 107 cfu/1ml of live Corynebacterium pseudotuberculosis through intradermal, intranasal and oral routes respectively. A significant decrease in red blood cell (RBC) count (p<0.05) in the intradermal infected with mean value of 11.3x109/L, while the packed cell volume (PCV), hemoglobin concentration (HbC) mean corpuscular volume (MCV), and mean cellular hemoglobin concentration (MCHC) remained unaltered. Significant increased (p<0.05) in white blood cells (WBC) were observed in all the inoculated groups-2, 3 and 4 with mean value of 13.68x109/L, 9.68x109/L, 8.67x109/L respectively. Significant increase (p<0.05) in monocyte count was observed in intranasal route with a mean of 0.754x10 9/L. A significant reduction (p<0.05) in lymphocytic count was observed for the intranasal inoculated group with a mean value of 3.37x109/L (p<0.05). Significant increase (p<0.05) in neutrophil was observed in intranasal and intradermal route with a mean of 8.80x10 9/L, 6.95x10 9/L, respectively. Creatinine levels increased (p<0.05) in the intranasal group with a mean of 91.33μmol/L while increased in GGT levels were observed (p<0.05) intradermal, intranasal and oral groups with a mean differences of 46.52U/L, 48.00U/L, 36.62U/L respectively. Lowered Calcium (Ca2+) concentrations were observed in the intradermal group with a mean concentration of 2.22mmol/L and 2.23 mmol/L for the intranasal group. Albumin levels were decrease (p<0.05) in the intranasal group with a mean of 28.74g/L. Plasma concentrations of progesterone were significantly (p<0.05) elevated in intranasal, oral and intradermal with a mean difference of 6.67pg/ml, 3.81pg/ml and 2.4pg/ml respectively. The plasma concentrations of estrogen were elevated significantly (p<0.05) in the oral route with a mean of 33ng/ml. However, slight rises in estrogen levels were observed in intradermal and intranasal routes in comparison with the control group. Interleukin-1β showed a significant increase (p<0.05) through the intranasal, intradermal and oral routes compared to the control group with a mean statistical difference of 99pg/ml, 67pg/ml, 42pg/ml respectively while interleukin-6 levels were significantly increased in the intranasal group 85pg/ml (p<0.05). There were no significant differences observed in intradermal and oral groups when compared to the control group. Histologically, inflammatory cells were observed as well as cellular necrosis, congestion in the ovary, uterine horn, cervix and vagina in intranasal and oral routes. Congestion, necrosis were observed in the ovary and uterine horn while necrosis and inflammatory cells were observed in the cervix and vagina of does inoculated through intradermal route. Lesions observed in uterus for the three groups are congestion, edema, necrosis and inflammatory cells. The present study, therefore, highlight the effects of C.pseudotuberculosis on blood, progesterone, estrogen, IL-1β, IL-6 and cellular changes in the reproductive organs and associated lymph nodes which is significant in the understanding the pathophysiology of reproductive system in does infected with C.pseudotuberculosis.